2022
DOI: 10.3390/polym14112279
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Graft Copolymers with N-Vinylimidazole as Promising Matrices for Immobilization of Bromelain, Ficin, and Papain

Abstract: This work aims to synthesize graft copolymers of chitosan and N-vinylimidazole (VI) with different compositions to be used as matrices for the immobilization of cysteine proteases—bromelain, ficin, and papain. The copolymers are synthesized by free radical solution copolymerization with a potassium persulfate-sodium metabisulfite blend initiator. The copolymers have a relatively high frequency of grafting and yields. All the synthesized graft copolymers are water-soluble, and their solutions are characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Finally, we compare the activity recovery of immobilized bromelain obtained in this work with our previously published results ( Figure 6 ). Earlier, we studied bromelain immobilization on chitosan (Ch) [ 46 ], 2-(4-acetamido-2-sulfanilamide) chitosan (SACh) [ 41 ], and chitosan copolymer with poly- N -vinylimidazole (Ch-g-PVI) [ 63 ]. As can be seen, the best activity recovery is achieved for bromelain immobilized on HTCCh and SACh, while for other proposed matrices, its value is dramatically low.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we compare the activity recovery of immobilized bromelain obtained in this work with our previously published results ( Figure 6 ). Earlier, we studied bromelain immobilization on chitosan (Ch) [ 46 ], 2-(4-acetamido-2-sulfanilamide) chitosan (SACh) [ 41 ], and chitosan copolymer with poly- N -vinylimidazole (Ch-g-PVI) [ 63 ]. As can be seen, the best activity recovery is achieved for bromelain immobilized on HTCCh and SACh, while for other proposed matrices, its value is dramatically low.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of grafting, FG , is expressed as the number of grafted polymer chains per anhydrous glucosamine unit, AGU , in the backbone polymer and is obtained from the relationship [ 21 ] where PVP , % is the percentage of grafted PVP in Cht- g -PVP; M PVP is the molecular weight of PVP; M AGU is the average weight of an anhydrous glucose unit of Cht; and Cht , % is the percent of Cht in Cht- g -PVP.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of grafting, FG, is expressed as the number of grafted polymer chains per anhydrous glucosamine unit, AGU, in the backbone polymer and is obtained from the relationship [21]…”
Section: Characterization Of Grafted Pvp Chainsmentioning
confidence: 99%
“…Moreover, it was shown that the grafting of poly( N -vinylimidazole) or poly( N , N -dimethyl amino ethyl methacrylate) (PDMAEMA) on Na-CMC macromolecules increases the loading and encapsulation efficiency of paclitaxel as compared to non-modified Na-CMC [ 12 , 13 ]. Paclitaxel is a plant-origin drug with a complex structure [ 14 ], so it can be suggested that incorporation of the side nitrogen-containing macromolecular substitutes may increase the interactions with other complex biostructures, e.g., enzymes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%